The Implementation of Prophet's Character Education at Al-Multazam II - Mukhlisin Mukhlisin; Rosdita Indah Yuniawati; Abdurrahman Atsa’lawi (Journal EduMasa Islamic Education, 2023)
The recent emergence of various social phenomena had prompted the government to formulate a national character development policy. The condition of the phenomena informed by electronic media or print media regarding drug cases, corruption, law violations, promiscuity among adolescents, cheating habits and bullying habits at schools indicate a shift towards implementing national identity and character. This study aimed to identify character education programs, the implementation of the Prophet’s character education, the impact of the Prophet’s character education on morals, and the supporting and inhibiting factors of the Prophet's character education at SMP IT Al Multazam II Kuningan. The research methodology used a qualitative approach which includes observation techniques, interviews and documentation studies. The results showed that character education programs included halaqoh, field trips, and Dedication. Character education impacts morals to Allah SWT, morals to humans, and increased achievement. The novelty of this study was that students have a balance of spiritual, emotional, intellectual and personal body health with morals, worship and social life.